SAT0387 Visualization of cartilage as a new imaging biomarker for the quantification of joint damage in rheumatoid arthritis using DGEMRIC and T2-mapping in high-resolution magnet resonance imaging. (23rd January 2014) - Herz, B.; Finzel, S.; Albrecht, A.; Rech, J.; Englbrecht, M.; Welsch, G.; Schett, G.
Abstract : Background: Recently, the gradient-echo-based T1-delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) has been developed for the detection of proteoglycan content in cartilage; moreover, multi-echo and spin-echo T2-mapping has become increasingly popular for the assessment of cartilage hydration and collagen microstructure. Current Magnetic Resonance Imaging (MRI)-studies conclude a link between dGEMRIC and T2 and early changes of cartilage in inflammatory diseases. Yet further validation studies on their diagnostic value in inflammatory diseases are needed. Objectives: To investigate the correlation between morphological and biochemical alterations in the cartilage of patients with Rheumatoid Arthritis (RA) by high-resolution 3Tesla-MRI. Methods: 29 RA-patients received a 3Tesla-MRI scan of the 2nd and 3rd metacarpophalangeal (MCP) joint of the dominant hand with 2 small-diameter surface coils designed for high-resolution imaging of cartilage (0.26×0.26×105mm voxel size; Verio Siemens Healthcare, Erlangen, Germany). T2-mapping and dGEMRIC were done. T2 and T1 relaxation times were obtained using a region-of-interest (ROI) evaluation. MCP heads and bases were scored semiquantitatively for synovitis, bone marrow edema (BME) and bone erosion (BE) using the RA MRI scoring (RAMRIS) system; joint space and cartilage thickness were measured perpendicular to the joint plane in all 3 joint regions (fig. 1a ). Results: For correlation analysis means of real and total joint spaces (RJS, TJS), RAMRIS-subscores, and ROIs of dGEMRIC- and T2-evaluations were used (fig. 1a : source data acquisition, fig. 1b : correlation analysis). Early changes of cartilage such as BME and synovitis in RAMRIS as compared to dGEMRIC were correlated negative (p=0.029; p=0.003); likewise, BME and synovitis showed positive correlation (p=0.013; p=0.015) in T2. In contrast, changes of periarticular structure occurring at later stages of the disease such as BE did not correlate with dGEMRIC (p=0.704) and weakly with T2 (p=0.026). All joint space subanalyses of MCP3 despite RJS correlated with dGEMRIC and T2 mainly in medial region (TJS p=0.017; TCT p=0.020; CT p=0.018). Additionally, in dGEMRIC MCP2 and RJS correlated in ulnar side (p=0.001). Conclusions: dGEMRIC and T2-mapping in high-resolution MRI enable exact detection of very early inflammatory changes in cartilage known to precede RA-typical periarticular bone damage. This is important both for early discovery of damages, adequate therapy decisions and -monitoring; this may also influence the development of future anti-inflammatory drugs. Additional studies on mechanical influences on cartilage are needed to further evaluate the mechanisms of joint space alterations. Disclosure of Interest: None Declared